Male and female identity and environmental contexts influence courtship behaviour in a songbird. (April 2022) - Canal, David; Jablonszky, Mónika; Krenhardt, Katalin; Markó, Gábor; Nagy, Gergely; Szász, Eszter; Török, János; Zsebők, Sándor; Garamszegi, László Zsolt
Abstract : Behavioural variation in courtship has become a central theme in the study of sexual selection. Courtship behaviour can vary consistently between males (between-individual variation) due to inherent characteristics of individuals, but males may also plastically adjust their courtship (within-individual variation) in response to the characteristics of the potential breeding mate or the environmental contexts. However, the relative importance of these components in courtship behaviour remains poorly understood. Here, we exposed male collared flycatchers, Ficedula albicollis, to different stimulus females simulating a female's visit to the male's territory during mate choice. We measured the male's latency to explicitly invite the female to visit the nestbox (hereafter, invitation latency), as a proxy of the male's motivation to mate. Repeated measurements of focal males (exposed to different stimulus females) and stimulus females (presented to different males) allowed us to assess the relative importance of male and female identity in male courtship, while also assessing the importance of their phenotype and other environmental sources of within-individual variation in invitation latency. We found that invitation latency was determined by male and, to a lesser extent, female identity, with the latter suggesting the existence of male mate choice in the species. We failed to identify specific traits of males and females that influenced courtship behaviour, although male responsiveness to stimulus females increased as the season advanced, possibly due to the costs of delaying breeding in temperate breeding areas. Overall, these results suggest that invitation latency is a consistent courtship attribute in males that can be adjusted plastically according to perceived female quality and environmental conditions. We emphasize that understanding within- and between-individual sources of courtship variation is essential for assessing its evolutionary potential, as plasticity in the expression of sexual signals may affect their reliability and the strength of sexual selection on them. Highlights: We simulated female visits to the male's territory and measured courtship. Courtship behaviour varied consistently between males. Males adjusted their courtship according to perceived female identity. Courtship behaviour was also sensitive to seasonality. Plasticity in sexual signal expression may affect the strength of sexual selection.